Spectrophotometric Determination of Sulphite in Various Water Samples Via Chromium-1,5-Diphenylcarbazide Complex (Baghdad Science Journal, 2018)
A simple and rapid spectrophotometric method for the determination of sulphite SO3-2 is described. The method is based on the rapid reduction of known amount of chromate CrO4-2 in the presence of sulphite in acidic medium of 2N H2SO4. The amount of excess of chromate was measured after it reactions with 1,5-diphenylcarbazide which finally gives a pink-violet, water soluble and stable complex, which exhibit a maximum absorption at 542 nm. Beer's law was obeyed in the concentration range from 0.004-6.0 µg of sulphite in a final volume of 25 ml with a molar absorbtivity of 4.64×104 l.mol-1.cm-1, Sandal's sensitivity index of 0.001724 ?g .cm-2 and relative standard deviation of ±0.55 - ±0.83 depending on the concentration level. The present method has been developed for the determination of sulphite in the presence of thiosulphate. Good recoveries of sulphite from various water samples are achieved using the proposed method.